Does flipped learning method via MOODLE can improve outcomes and motivation of discrete mathematics learning during COVID-19 pandemic? - Mursyidah, H; Hermoyo, R P; Suwaibah, D (Journal of physics. Conference series, 2021)
The purpose of this study is to determine whether the flipped learning method via MOODLE can improve learning outcomes and motivation to learn discrete mathematics during COVID-19 pandemic. This is because discrete mathematics is one of the mathematics subjects that requires a lot of practice and needs direct direction by lecturers or educators. In this study, we used Classroom Action Research that consisted of two cycles. The stages in each cycle were plan, implementation, observation, and reflection. Based on the results of the study, it was found that the flipped learning method via MOODLE can improve the learning outcomes of discrete mathematics from only 30% of students who complete to 100% of students completed. In addition, students' discrete mathematics learning motivation increased from 45% or medium criteria to 79% or high criteria. The stages that can be used are (1) lecturers provide stimulus through questions to students to find references independently of a question, (2) students learn the material independently and make questions about the material which is not yet understood, (3) students and lecturers conduct discussions to correct misconceptions, and (4) students work on questions from lecturers as evaluation.